2013
DOI: 10.4172/2157-7579.1000127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Study of the Bovine Sarcocystis Species in the Slaughterhouses of Rouiba (Algiers)

Abstract: In this present study, experimental infestations of the definitive hosts of cattle Sarcocystis were realized to identify the species existing in our regions. For that purpose, 200 g of a mixture of oesophagi and diaphragms infested by cysts of Sarcocystis were administered to 7 dogs, 2 cats and 2 Magot monkeys. Only dogs excreted oocystes and sporocystes of Sarcocystis cruzii, although cysts with thick wall were present in broyats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The same experiment was reproduced by the team of Aissi et al (2013), who found oocysts S. cruzi after infestation of cats, dogs and primates (maggot monkeys) by portions of muscle infested with microscopic cysts.…”
Section: Breed Factormentioning
confidence: 93%
“…The same experiment was reproduced by the team of Aissi et al (2013), who found oocysts S. cruzi after infestation of cats, dogs and primates (maggot monkeys) by portions of muscle infested with microscopic cysts.…”
Section: Breed Factormentioning
confidence: 93%